Efficacy of the subthreshold micropulse yellow wavelength laser photostimulation in the treatment of chronic central serous chorioretinopathy - Mehmed Uğur Işık; Mehmet Fatih Kağan Değirmenci; Ayhan Sağlık (Press of International Journal of Ophthalmology (IJO Press), 2020)
To evaluate the efficacy and safety of subthreshold micropulse yellow laser (SMYL) in the treatment of chronic central serous chorioretinopathy (CCSC).The medical records of 58 eyes of 58 patients with CCSC were reviewed. A 577-nm SMYL system was used for the treatment. Fundus fluorescein angiography was used as the primary method of identifying CCSC, and resolution of subretinal fluid (SRF) evaluated by optical coherence tomography (OCT) and fundus autofluorescence. Central macular thickness (CMT), central macular volume (CMV), total macular volume (TMV), subfoveal choroidal thickness (SFCT), subretinal fluid height (SRFH), and subfoveal fluid basement diameter values were measured by spectral domain-OCT (SD-OCT) for all eyes.The mean age of the patients was 42.4±9.9 (range: 20-72)y. The mean follow-up was 11.4±8.5 (range: 6-37)mo. Median BCVA at at the final follow up after treatment was statistically significant from the baseline. Complete SRF resolution was 12.1% of the eyes in the 1st month, 67.2% of the eyes in the 3rd month and 67.2% of the eyes in the last follow up. The initial median CMT, CMV, TMV, and SFCT values before treatment was significantly higher than 3rd month visit values (P<0.001). In the multivariate analysis performed, age and disease duration were found to be a risk factor for persistent SRF (P=0.017, P=0.016, respectively).SMYL treatment provides a significant anatomical and functional improvement and is effective in eliminating SRF in eyes with CCSC.
Keywords: Ophthalmology; optical coherence tomography; subthreshold micropulse laser; RE1-994; central serous chorioretinopathy; 3. Good health